ANALISIS PENGARUH DANA PIHAK KETIGA, TINGKAT SUKU BUNGA, DAN NON PERFORMING LOAN TERHADAP PENYALURAN KREDIT UMKM PADA BANK UMUM DI INDONESIA - Aldila, Gaby Firdha (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2012)
His study is a case study on commercial banks in Indonesia with the title of Analisis Pengaruh Dana Pihak Ketiga, Tingkat Suku Bunga, dan Non Performing Loan Terhadap Penyaluran Kredit UMKM Pada Bank Umum di Indonesia tahun 2007:1 – 2010:12. Based on the results showed that during the study period is partially funding a third party, the interest rate, and non-performing loans have a significant effect on SME lending. While simultaneously obtained that third party funds, interest rate, and non-performing loans have a significant effect on SME lending. The magnitude of these effects is 0.988 or 98.8%. While the remaining 1.2% is affected by other factors outside of the study, or outside the regression equation